A Analyzing the content of mathematics books for the upper primary stage according to the skills of creative solving verbal problems (Journal of the College of Basic Education, 2024)
The aim of the research is to analyze the content of the mathematics books of the upper primary stage according to the skills of creative solving of verbal problems, and to verify the goal of the current research, the following questions were derived:1) What are the creative solving skills of verbal problems in the content of mathematics books for the upper primary stage?2) What are the skills of creative solving verbal problems in the content of the mathematics textbook for the fourth grade of primary school3) What are the skills of creative solving verbal problems in the content of the mathematics textbook for the fifth grade of primary school4) What are the creative solving skills of verbal problems in the content of the mathematics textbook for the sixth grade of primary school In order to achieve the goal of the current research, the researcher adopted the descriptive analytical approach, and determined the study community by the content of mathematics books for the upper primary stage . The main and sub-skills for creative solving verbal problems and their indicators, where the number of main skills was (3) skills, (10) sub-skills, and (31) indicators indicative of which were verified by their validity and stability . The explicit and implicit idea as a unit of analysis, frequencies, percentages, and the Holesti equation ) as statistical means, and the stability coefficient of the analysis was calculated over time and across analysts, and the results showed the following:1) upper primary stage contains low percentages of creative solving skills for verbal problems, as its repetitions in all the content of the three books mentioned above reached ( 7315 ) recurrences.2) The skill (understanding the problem) achieved the first rank in the content of each of the mathematics textbooks for the upper primary stage, followed by the skill (generating ideas) in the second rank, and then the skill (planning for implementation) in the third rank. In light of the results of the study, the researcher Tan presented some of the recommendations and proposals, most notably, reconsidering the formulation of the content of mathematics books for the upper primary stage , by employing creative solutions to verbal problems in high and equal proportions in their content. According to the creative solving skills of verbal problems and the extent to which students have acquired them.